Kinetics of Changes Induced by Indigenous Microbiota in the Activity Levels of Alkaline Phosphatase and Disaccharidases in Small Intestinal Enterocytes in Mice - Whitt, Dixie D. (1980)
The concentration of protein and the activities of alkaline phosphatase, maltase, and sucrase were measured in saline extracts of the proximal small intestine of germfree and ex-germfree mice colonized with an indigenous microflora. The two populations of animals were maintained in plastic film isolators under tightly controlled environmental and nutritional conditions. Samples were taken at 0, 4, 8, 12, and 17 days and at 3, 4, 5, 6, 7, and 8 weeks after association. The activities were expressed as specific activities and as total units per segment of small intestine. Enzymatic activities expressed in both ways fluctuated considerably in the samples taken from one time to the next in animals of both types. The activities expressed as total units per segment of bowel of all three enzymes had decreased from levels in germfree animals by as early as 4 days after association. The total units of activity per segment of bowel tested continued to decrease for approximately 3 weeks in the associated animals to levels two- to fivefold lower than those of germfree animals. However, the specific activities of the three enzymes in the animals of the two types became less disparate at later sample times. This latter result is predictable because the concentration of protein extractable from the small intestines of the mice of the two types was the same at the beginning of the experiment, but by the later sampling times, the concentration of protein extractable from small bowels of ex-germfree mice was significantly lower than that from germfree mice. The fluctuations in levels of the enzymatic activities, even under controlled environmental and nutritional conditions, point to the necessity of using such conditions and a kinetic approach in studies of the effects of the microbiota on the activities of enzymes in the microvillous membranes of small bowel enterocytes. The changes in protein concentrations suggest that such activities and the amounts of protein extractable from the mucosa are influenced by different properties of the microflora. Thus, studies in which the enzymes are extracted from the entire mucosa and the activities are expressed as units per weight of extractable protein may give misleading results concerning the influence of the microbiota on the enterocyte membranes.